World education patterns in the global South : the ebb of global forces and the flow of contextual imperatives - Wolhuter, C. C. (Charl C.) (International perspectives on education and society, 2022)
World Education Patterns in the Global Southsurveys the educational responses and new educational landscapes being developed as a consequence of the powerful global forces that are demanding change within the Global South's educational contexts, including Central and South-East Asia, Latin America, and the Caribbean.